Iodine-induced coupling reaction forms C–S and C–N bonds to construct 3, 4-heteroatom-Functionalized maleimides. (24th September 2021) - He, Xiao-long; Wen, Si-yu; Tang, Xue; Yu, Zi-hua; Huang, Cheng-xi; Li, Yu-jin
Abstract: Using iodine to induce the intermolecular thioamination reaction of maleimide, thiol and amine, various kinds of substituted 3-amino-4-thiomaleimides were obtained in good yields. This reaction was performed in THF at the presence of I2 and TBHP. On the basis of optimized conditions, a variety of thiophenols and amines were involved in the reaction. The method provided a new and green way for the thioamination of maleimide, in which heavy metal was avoided to use. Graphical abstract: Image 1